2016
DOI: 10.7717/peerj.2651
|View full text |Cite
|
Sign up to set email alerts
|

Building healthy eating habits in childhood: a study of the attitudes, knowledge and dietary habits of schoolchildren in Malaysia

Abstract: BackgroundOverweight and obesity have increased rapidly in incidence to become a global issue today. Overweight and obesity problems are significantly linked to unhealthy dietary patterns, physical inactivity and misperception of body image. This study aimed to determine whether Malaysian children build healthy eating habits from childhood.MethodsA survey on eating habits was conducted among primary school students in standards 4 to 6 in the state of Selangor, Malaysia. The findings of the study were reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 19 publications
3
17
0
3
Order By: Relevance
“…Moreover, (Melhem and Al-Wedian, 2013) study indicates that students' degree of commitment to health food habits and behaviors is high. The highest mean of this study was (4.77) for statement 16 "Ensure the cleanliness of food before eating it"), and this result was agreed with Hoque et al (2016), which indicated that the most important factor for students to make a decision on food, (65.8%) of them chose its cleanliness. This finding differed with the Cefai and Camilleri (2011), Walid et al (2015), Samia and Abd El-Mouty (2016) and Abraham and Noriega (2018), all of which indicated that there were unhealthy food habits and behaviors in different samples and countries where these studies were applied.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, (Melhem and Al-Wedian, 2013) study indicates that students' degree of commitment to health food habits and behaviors is high. The highest mean of this study was (4.77) for statement 16 "Ensure the cleanliness of food before eating it"), and this result was agreed with Hoque et al (2016), which indicated that the most important factor for students to make a decision on food, (65.8%) of them chose its cleanliness. This finding differed with the Cefai and Camilleri (2011), Walid et al (2015), Samia and Abd El-Mouty (2016) and Abraham and Noriega (2018), all of which indicated that there were unhealthy food habits and behaviors in different samples and countries where these studies were applied.…”
Section: Discussionsupporting
confidence: 78%
“…More than three-quarters of the sample (83%) had a weak knowledge of the healthy diet, and the study proved that students practiced many unhealthy eating habits on campus, and there are many factors attributed to eating habits that can be either individual or factors which enable students to easily access unhealthy foods. Hoque et al (2016) aimed at building healthy food habits in childhood and studying attitudes, knowledge and eating habits of schoolchildren in Malaysia. To achieve this goal, a survey was conducted on the food habits of the sample of 400 primary school students in standards 4 to 6 in the state of Selangor, Malaysia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…15 In a similar study carried out amongst Malaysian school children 31% consumed milk and dairy products daily while around 20% consumed vegetables daily and 30% of the children consumed fruits daily. 16 Nearly 60% of them preferred fried food like hamburger and fries despite knowing that these were unhealthy food preferences .A similar finding was also reported from a study carried out in Korea where it was noted that school children in both urban and suburban areas preferred fast foods like pizzas. 17 In our study the mother's educational status was not found to be significantly associated with the frequency of consumption of any particular food item.…”
Section: 10supporting
confidence: 70%
“…Children spend significant amounts of time (i.e., 6-9 hours) in the school environment daily which may influence their food choices and shape their attitudes towards foods offered in the school [38]. Thus, schools provide a critical opportunity for promoting healthy food choices and optimal dietary behaviors [37,38,39,40,41,42]. There is inadequate data on dietary intake and food choices in school children, especially in African settings [32].…”
Section: Introductionmentioning
confidence: 99%